Odoevsky's four pathways into modern fiction a comparative study - Cornwell, Neil.; ebrary, Inc. (Manchester ; New York : Manchester University Press : Distributed in the United States exclusively by Palgrave Macmillan, 2010)
This book takes four stories by the Russian romantic author Vladimir Odoevsky to illustrate 'pathways', developed further by subsequent writers, into modern fiction.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: q -- 1804-1869 -- Criticism and interpretation; q -- 1804-1869 -- Translations into English; Romanticism; Fiction genres; Fiction -- 19th century -- History and criticism; Fiction -- 20th century -- History and criticism; Electronic books